Cross Cultural Interaction of Japanese Retirees through Clubs in Thailand - Duangkaew, Sutpratana (Asian Crime and Society Review, 2019)
Expat living is an increasing phenomenon in the 21st century. This involves not only people from developing countries moving to developed countries for economic or life security reasons, but also, conversely, some retirees from developed countries decide to live in a less developed country as a second home. This paper explores the mobility of Japanese retirees in Chiang Mai and explains the situation of cross-cultural interaction between the retirees and the locals through Japanese clubs, based on the social capital (SC) conception. The data was collected by interviews from 2013 to 2015 and 2019. In conclusion, three kinds of SC stimulated the exchange of Japanese clubs and the locals. For the act of bonding SC, they shared and interacted within their group, comprised of the people who have the same nationality and hobbies. For bridging SC, there were connections among Japanese clubs and organizations from Japan. Lastly, for linking SC, being a club member privileges them to participate in the club’s recreation and volunteering activities, which becomes a channel for them to get to know the local people. Through these cultural exchange activities, the Japanese can gain a better understanding of Thai culture by promoting co-existence.